Microplastic sampling and biological effects assessment - Dee, Pei Fang (2019)
Reports of microplastic contaminants found in marine ecosystems and foods have increasingly raised concerns. Uptake of nanosized polystyrene was reported to affect the mortality and reproduction of marine organisms such as mussels and copepods. However, little is known about the degree of microplastic exposure and their potential biological effects to humans. Recent in vivo tests subjecting human cerebral T98G cells, cervical epithelial HeLa cells and colon Caco-2 cells to polystyrene particles reported reactive oxygen species (ROS) effects. In this study, cell viability assays of human gastric adenocarcinoma MKN45 cells and human colon NCM460 cells showed varying cellular responses upon direct exposure to polystyrene particles of different sizes. Although NCM460 cell growth was not significantly affected, 2 days of exposure to 0.1 mg/mL polystyrene fragments of size 200 nm caused higher proliferation rate in MKN45 cells compared to 20 nm polystyrene fragments or control cell culture medium, suggesting oxidative stress-induced proliferation. Therefore, assessing the direct intake of microplastics and nanoplastics is needed for future studies on human gut exposure. To examine microplastic contamination in drinking water, a Nile Red staining procedure from literature was adapted to collect microplastics from readily available bottled drinking water. The protocol developed can be easily replicated in laboratories with fluorescence microscope. A small sampling of drinking water from 1.5-litre bottles conducted with the customised protocol confirmed the presence of trace quantities of microplastics not significantly more abundant than in indoor environment. Furthermore, two weeks of freezing to as low as -20ºC simulating freezer storage and heating bottled water at 60ºC simulating storage in hot cars caused slight deformation of plastic bottles but microplastic particles collected were similar in size distribution. No significant increases in particle quantity were observed, thus showing no increase in risks regardless of storage temperature.